An Intelligent Supplementary Lighting System for the Strawberry Greenhouse - Zhiliang Kang; Lijia Xu; Fei Xiao (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
An intelligent supplementary lighting system for a strawberry greenhouse is developed in this study using the embedded controller S3C6410 as core. This system detects the temperature and lighting information of the strawberry greenhouse with the temperature sensor DS18B20 and the lighting sensor 2DU6. It stores, displays, analyzes, and processes the collected information with S3C6410 and transfers the control commands to STC89C52 through APC220-43. Thus, it realizes temperature regulation of the strawberry greenhouse and intelligent supplementary lighting of red–blue LED combined lights. The test result shows that this system not only realizes supplementary lighting as required and by wave bands, but also saves electric power. This system has distinctive features of strong applicability, good expandability, stable and reliable operation, and visual and simple control.